Conversion of oil shale to liquid hydrocarbons. Issue 18 (16th September 2016) - Demirbas, Ayhan
ABSTRACT: Oil shale is a complex fossil material that is composed of organic matter and mineral matrix. The thermal decomposition of the organic matter generates liquid and gaseous products. Oil shale is a porous rock containing kerogen, an organic bituminous material. Kerogen is a solid mixture of organic compounds that is found in certain sedimentary rocks. The kerogen can be pyrolyzed and distilled into petroleum-like oil. Oil shale and bituminous materials are suitable for obtaining petroleum-like products. The process designed in this study has the ability to control unwanted volatile materials. The mineral matter is removed from oil shale before pyrolysis. The pyrolysis of the oil shale is performed in a retort. The temperature at which the kerogen decomposes into usable hydrocarbons begins at 300°C, but the decomposition proceeds more rapidly and completely at higher temperatures. Decomposition takes place most quickly at a temperature between 475 and 525°C. Shale oil from oil shale consists of the hydrocarbons: paraffins, olefins, isoparaffins and naphthenes, isoolefins and cycloolefins, monocyclic aromatics, and poly-cyclic aromatics. The nonhydrocarbons are nitrogen, sulfur, and oxygen (NSO) compounds.